The impact of school culture on the mental health of female students - Silkey Chaudhary, Dr. Vibha Nagar, (International Journal of Scientific Research and Management (IJSRM), 2017)
The purpose of this research paper was to find out the impact of school culture on the mental health of Vedic & Non-Vedic School girls who were studying in class 8 th -12th (age range: 14 to18years).This is a comparative study of mental health among the girls studying in Vedic & Non-Vedic Schools. The sample consisted of 100 Vedic & Non-Vedic School girls selected randomly (50 girls from each school). Mental Health check list developed by Kumar was used for measuring the mental health. “t-Test” was used for analyzing the data. The Results showed that there is a significant difference of 0.01 among the mental health of Vedic & Non-Vedic school girls. The girls of Vedic School girls have better mental health as compared to girls of Non Vedic schools